INTERVENTIONS TO LOWER HIGH BLOOD PRESSURE IN PREGNANT WOMEN: A LITERATURE REVIEW - Mamuroh, Lilis; Nurhakim, Furkon; Sukmawati, Sukmawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
One of the problems that often arises in pregnant women is hypertension. Hypertension in pregnancy is caused by changes in the cardiovascular system and blood vessels. Hypertension in pregnancy accounts for 5–15% of pregnancy complications and is one of the three highest causes of maternal mortality and morbidity. The purpose of this study was to determine the various nursing interventions that can be done to reduce high blood pressure in pregnant women. This study uses a literature review system with PRISMA to facilitate the process of finding suitable articles. After searching and analyzing, there were 7 articles that were judged to meet the criteria. Of the 7 articles, 6 different interventions have been shown to reduce blood pressure: yoga therapy, TFA diet therapy, mushroom diet therapy, spiritual therapy, Turkish classical music therapy, folic acid supplement therapy, and murrotal therapy. Of the 7 interventions that have been studied, 6 have been shown to reduce blood pressure in pregnant women.